Effect of titanium implants along with silver ions and tetracycline on type I interferon-beta expression during implant-related infections in co-culture and mouse model - Rahim, Muhammad Imran; Waqas, Syed Fakhar-ul-Hassnain; Lienenklaus, Stefan; Willbold, Elmar; Eisenburger, Michael; Stiesch, Meike (Frontiers in Bioengineering and Biotechnology, 2023)
Type I interferon-beta (IFN-β) is a crucial component of innate and adaptive immune systems inside the host. The formation of bacterial biofilms on medical implants can lead to inflammatory diseases and implant failure. Biofilms elicit IFN-β production inside the host that, in turn, restrict bacterial growth. Biofilms pose strong antibiotic resistance, whereas surface modification of medical implants with antibacterial agents may demonstrate strong antimicrobial effects. Most of the previous investigations were focused on determining the antibacterial activities of implant surfaces modified with antibacterial agents. The present study, for the first time, measured antibacterial activities and IFN-β expression of titanium surfaces along with silver or tetracycline inside co-culture and mouse models. A periodontal pathogen: Aggregatibacter actinomycetemcomitans reported to induce strong inflammation, was used for infection. Silver and tetracycline were added to the titanium surface using the heat evaporation method. Macrophages showed reduced compatibility on titanium surfaces with silver, and IFN-β expression inside cultured cells significantly decreased. Macrophages showed compatibility on implant surfaces with tetracycline, but IFN-β production significantly decreased inside seeded cells. The decrease in IFN-β production inside macrophages cultured on implant surfaces with silver and tetracycline was not related to the downregulation of Ifn-β gene. Bacterial infection significantly upregulated mRNA expression levels of Isg15, Mx1, Mx2, mRNA expression levels of Mx1, Irf7, Tlr2, genes inside macrophages significantly downregulated on implant surfaces with silver or tetracycline. Titanium with tetracycline showed higher antibacterial activities than silver. The in vivo evaluation of IFN-β expression around implants was measured inside transgenic mice constitutive for IFN-β expression. Of note, the non-invasive in vivo imaging revealed a significant decrease in IFN-β expression around subcutaneous implants with silver compared to titanium and titanium with tetracycline in sterile or infected situations. The histology of peri-implant tissue interfaces around infected implants with silver showed a thick interface with a significantly higher accumulation of inflammatory cells. Titanium implants with silver and tetracycline remained antibacterial in mice. Findings from this study unequivocally indicate that implant surfaces with silver decrease IFN-β expression, a crucial component of host immunity.